Secret sisters [large type] - Krentz, Jayne Ann (Thorndike Press, A part of Gale, Cengage Learning, 2015)
Madeline and Daphne were once as close as sisters--until a secret tore them apart. Now it might take them to their graves. They knew his name, the man who tried to brutally attack twelve-year-old Madeline in her grandmother's hotel. They thought they knew his fate. He wouldn't be bothering them anymore...ever. Still their lives would never be the same. Madeline has returned to Washington after her grandmother's mysterious death. And at the old, abandoned hotel--a place she never wanted to see again--a dying man's last words convey a warning: the secrets she and Daphne believed buried forever have been discovered. Now, after almost two decades, Madeline and Daphne will be reunited in friendship and in fear. Unable to trust the local police, Madeline summons Jack Rayner, the hotel chain's new security expert. Despite the secrets and mysteries that surround him, Jack is the only one she trusts...and wants. Jack is no good at relationships but he does possess a specific skill set that includes a profoundly intimate understanding of warped and dangerous minds. With the assistance of Jack's brother, Abe, a high-tech magician, the four of them will form an uneasy alliance against a killer who will stop at nothing to hide the truth....